Comparative study of various protocols of DDS. Issue 4 (4th July 2017) - Kaushik, Shivkant; Poonia, Ramesh C.; Khatri, Sunil Kumar
Abstract: In this paper the comparison of various protocols of Dynamic Discovery Service is studied. This paper outlines the initiatives focused on discussing and understanding various DDS protocols on the basis of their common features. The comparison is structured by taking various features as the base for this comparison. Service Discovery Protocol (SDP), Jini, Salutation, Service Location Protocol (SLP), Secure Pervasive Discovery Protocol (SPDP), Universal Discovery Description and Integration (UDDI), and Universal Plug and Play (UPnP) are discussed briefly in this paper.